Studi Hadis tentang Menerima Hadiah dari Non Muslim - Febri Rahma Despi; Yulia Rahmi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
A gift is a gift from someone to another without any compensation. In the hadith of the Prophet there is the permissibility of accepting gifts from non-Muslims, but in several other narrations we find information about the Prophet's reluctance to accept gifts from non-Muslims. This is the background to the hadith study, whether this hadith can be accepted or rejected based on the calibre and comprehension of the hadith. through assessing the calibre and comprehension of hadith. This study is an example of a qualitative library research project. The book Mu'jam al-Mufahras li Alfazh al-Hadith al-Nabawi was utilised to trace the hadith based on word pronunciations, employing the takhrij hadith method as the data gathering strategy for this study. The data analysis technique, on the other hand, employs Yusuf Al-Qardhawi's ma'anil hadith method, which consists of three steps: comprehending the hadith in accordance with the Qur'anic instructions, comprehending the hadith by gathering similar hadith, and comprehending by taking into account the situation's conditions and goals. The outcomes of hadiths of receiving gifts from non-Muslims found in the books of Sunan Abu Dawud and Sunan Tirmidhi are considered to be Hasan Lighairihi's sanad lines due to the quality of Ahmad bin Hanbal's authentic Musnad sanad lines. Meanwhile, the understanding of the hadith regarding accepting gifts from non-Muslims is that the Prophet's reluctance in accepting gifts from non-Muslims is closely related to the situation and conditions at the time the hadith appeared, namely the aqeedah which was still not strong, they were worried about their offering material and they were afraid that the gift would be bribery element.